Medical high-entropy alloy: Outstanding mechanical properties and superb biological compatibility - Liu, Changxi; Yang, Chengliang; Liu, Jia; Tang, Yujin; Lin, Zhengjie; Li, Long; Liang, Hai; Lu, Weijie; Wang, Liqiang (Frontiers in Bioengineering and Biotechnology, 2022)
Medical metal implants are required to have excellent mechanical properties and high biocompatibility to handle the complex human environment, which is a challenge that has always existed for traditional medical metal materials. Compared to traditional medical alloys, high entropy alloys (HEAs) have a higher design freedom to allow them to carry more medical abilities to suit the human service environment, such as low elastic modulus, high biocompatible elements, potential shape memory capability. In recent years, many studies have pointed out that bio-HEAs, as an emerging medical alloy, has reached or even surpassed traditional medical alloys in various medical properties. In this review, we summarized the recent reports on novel bio-HEAs for medical implants and divide them into two groups according the properties, namely mechanical properties and biocompatibility. These new bio-HEAs are considered hallmarks of a historic shift representative of a new medical revolution.